Phosphorus Dynamics in Managed and Natural Soils: SEM-PLS Analysis of Vaccinium, Forest, and Grassland Ecosystems - Chun Lu; Soh Sugihara; Satoshi Noma; Haruo Tanaka; Ryosuke Tajima; Shingo Matsumoto; Dai Hirose; Xueyan Zhang; Ning Wang; Takuya Ban (Plants)
Phosphorus (P) availability in soils is often constrained by its accumulation in non-labile phosphorus (NLP) forms, limiting its accessibility to plants. This study examines how soil physical properties, chemical characteristics, and climatic conditions influence phosphorus fractionation and the transformation of NLP into plant-available labile phosphorus (LP). Utilizing global structural equation modeling (SEM), we found that silt content enhances organic phosphorus fractions, including NaHCO3-Po and NaOH-Po. In the upper 30 cm of soil, pH decreases the availability of NaHCO3-Po and NaOH-Po while stabilizing NLP, highlighting its essential role in phosphorus cycling under acidic conditions. In deeper soil layers, pH facilitates phosphorus mobilization from NLP pools, with effects varying across fractions. Long-term studies on Japanese Vaccinium soils reveal that pH and electrical conductivity (EC) management significantly promote NLP-to-LP conversion, primarily through NaOH-Po, thereby improving phosphorus use efficiency. These findings underscore the critical importance of prioritizing chemical property management over physical modifications to optimize nutrient cycling, preserve soil fertility, and reduce reliance on external phosphorus inputs in agricultural systems. Our study emphasizes the need for integrated approaches to achieve sustainable phosphorus management in both natural and managed ecosystems.